ANALYZING THE GOVERNMENT OF BANDUNG CITY'S INNOVATIONS IN POPULATION SERVICES DURING THE COVID-19 PANDEMIC - Karniawati, Nia; Raihan Majid, Zidan; Anindia, Haura (Universitas Pancasakti Tegal, 2023)
The purpose of this research is to analyze the innovations that have been carried out by the Bandung City Government in population services during the Covid-19 Pandemic. This innovation is part of the bureaucratic reform of the Bandung City Government in an effort to improve public services. From this research, it will be known the efforts that have been made by the Bandung City Government in providing population services to the community during the Covid-19 Pandemic.